(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article concerns the question of developing system-creative thinking in the classes of English. It contains the description of some of the creative technologies (cluster, mind map, cubing) featuring their positive aspects. The author considers her own experience of using the technologies and their impact on students» system-creative thinking